The Relative Utility of Concurrent Sources of Information for Diagnosis of Autism Spectrum Disorder in Early Childhood - Arastoo, Sara; Abdullah, Maryam M.; Youssef, Julie; Guo, Yuqing; Schuck, Sabrina E. B.; Goldberg, Wendy A.; Donnelly, Joseph; Lakes, Kimberley D. (Frontiers in Pediatrics, 2020)
The development of effective screening methods for Autism Spectrum Disorder (ASD) in early childhood remains a public health priority for communities around the world. Little is known regarding the concurrence between parent concerns about ASD and formal ASD diagnostic methods. This study aimed to examine the relationships among a priori parental ASD concern, ADOS classification, and a physician specialist's diagnosis. One hundred and thirty-four toddlers (74% male; mean age = 31.8 months, SD 4.4) received an evaluation at a university center specializing in ASD and neurodevelopmental disorders. Correspondence between a priori parental ASD suspicion and physician diagnosis of ASD was 61% (p = 0.028). Correspondence between a priori parental suspicion of ASD and ADOS ASD classification was 57% (p = 0.483). Correspondence between ADOS classification and physician diagnosis of ASD was 88% (p = 0.001). Our results have implications for evaluations in low resource regions of the world where access to physician specialists may be limited; the high correspondence between ADOS classification and a physician specialist's diagnosis supports the use of trained ADOS evaluators, such as field health workers or early childhood educators, in a tiered screening process designed to identify those most in need of a specialist's evaluation. Our results also have implications for public health efforts to provide parent education to enable parents to monitor their child's development and share concerns with their providers. Parent awareness and expression of concern coupled with timely responses from providers may lead toward earlier identification of ASD, and other neurodevelopmental disorders, and hence, generate opportunities for earlier and more personalized intervention approaches, which in turn may help improve long-term outcomes. Empowering parents and community members to screen for ASD may be especially important in regions of the world where access to formal diagnosis is limited.